INVESTASI PT. SAIPEM INDONESIA DI KARIMUN STUDI KASUS PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP MASYARAKAT LOKAL - Dewi, Laksmita; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is the study of International Political Economy of Investment Pt. Saipem Indonesia Karimun Study Case Program In Corporate Social Responsibility (Csr) To The Local Communities. Karimun District that has been as created Free Trade Zone (FTZ) and Special Economic Zone (SEZ) created opportunities for Italia to invest in Karimun. Italia investment is poured through PT. Saipem Indonesia that was attended on 2007 in Karimun District. Operation of PT. Saipem Indonesia in Karimun District increased economic growth in Karimun district. This research used qualitative methods and library research. The theoretical framework applied in this research are neoliberalism perspective from David Harvey, the level of the nation-state analysis, the concept of national interest, international investment theory from Kindley Berger and monopolistic advantages theory from Stephen Hymer.The research shows that investment Pt. Saipem Indonesia Karimun Study Case Program In Corporate Social Responsibility (Csr) Against Local Communities provided great contributions and continue to implement corporate social responsibility in the form of sustainable development. With the implementation of the activities of Corporate Social Responsibility (CSR) is divided into three main areas, namely in the areas of environment, economics and social areas with the objective of sustainable development can be felt constantly by local communities.Keywords: PT. Saipem Indonesia, Investment, Corporate Social Responsibility (CSR), local communities, economic growth